2018
DOI: 10.1002/chem.201704924
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Ionic Liquid Cytotoxicity and Liposome–Ionic Liquid Interactions

Abstract: This study aims at extending the understanding of the toxicity mechanism of ionic liquids (ILs) using various analytical methods and cytotoxicity assays. The cytotoxicity of eight ILs and one zwitterionic compound was determined using mammalian and bacterial cells. The time dependency of the IL toxicity was assessed using human corneal epithelial cells. Hemolysis was performed using human red blood cells and the results were compared with destabilization data of synthetic liposomes upon addition of ILs. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 46 publications
(70 reference statements)
4
50
1
Order By: Relevance
“…Where It is the total intensity of the (0 0 2) peak for cellulose I and Ia is the intensity assigned to the amorphous cellulose. [51][52][53] . In addition, the IL welded CNFFs have changed their UV-Vis transmittance, suggesting that in some cases, IL might also remain attached to the films.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…Where It is the total intensity of the (0 0 2) peak for cellulose I and Ia is the intensity assigned to the amorphous cellulose. [51][52][53] . In addition, the IL welded CNFFs have changed their UV-Vis transmittance, suggesting that in some cases, IL might also remain attached to the films.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“… Membrane damage has been observed in red blood cells (RBC) incubated in [C 4 mim][Br], [C 10 mim][BF 4 ], and [BTDA][Cl] (Thamke et al 2017 ). Destabilization of the plasma cellular membrane of human corneal epithelial HCE cells and hemolysis of RBCs have been observed after incubation in [P 14444 ][Cl] and [P 14444 ][OAc] (Ruokonen et al 2018 ). In the same study, it has been shown that these two ILs switch the zeta potential of model lipid liposomes from negative to positive, evidencing a strong and possibly irreversible sorption of the ILs into the liposome.…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
“…Human corneal epithelial (HCE) cells were employed as representative model cells. A wide variety of ILs were selected and the metabolic profiles measured after incubation of the HCE cells with ILs at concentration levels corresponding to their median effective concentration (EC 50 ) values [4]. Here we will demonstrate that there is a correlation between the changes in the metabolic profiles and the toxicity of the ILs.…”
Section: Introductionmentioning
confidence: 84%
“…Since they are non-flammable, non-explosive, and non-volatile, they are used in many applications, also owing to their large range of solubilities and miscibilities. Their lack of biodegradability, however, renders toxicity studies imperative [4,5]. This matter is complicated because of the high structural variability and large number of existing ILs, requiring a differentiated picture of toxic effects of ILs [1,6,7].…”
Section: Introductionmentioning
confidence: 99%